Fabricação de blocos de concreto com substituição parcial do agregado miúdo por escória de fornos de fundição de chumbo - Trindade, Davi Graize (2020)
Clean technologies at a competitive cost have caused companies to review their policies prioritizing these solutions. This work aims to explore alternatives for reuse of waste from lead smelting industries, composed of high iron content and its granulometry makes it used to increase the strength of concrete blocks and create a sustainable alternative for final disposal environmentally of this type of waste. The existing compounds in these materials make it possible to use this industrial residue in the manufacture of concrete blocks as an optional technological raw material to partially compose the composition of aggregates. This work seeks an economically viable and environmentally safe outlet for this waste, which currently has been stored by industries for later disposal in landfills, due to the high cost of treatment and the lack of alternative technologies for recycling. The proposed solution intends to incorporate the slag from smelting furnaces of lead recycling companies, residue from the recycling of lead from car batteries. Research indicates that lead slag is composed primarily of iron, leading to physical and chemical improvements in concrete blocks, in addition to providing economic gains to the lead recycling sector and precast block production companies. Through the reuse of slag from foundry furnaces it is possible to reduce the emission of pollution, gaining the environment with cleaner practices and industries with more sustainable business models. Up to the present moment, the results have shown that block mixtures with 20% slag, have resistance to simple compression superior to the conventional block, asserting itself as a technically viable method. The results of the physical chemical analyze allowed to evaluate how safe the use of this residue in cement mixtures.